ISOLATION OF SULPHATE POLYGALACTAN FROM Eucheuma alvarezii Doty AND ITS ANTICOAGULANT ACTIVITY - ., Sutrisno; ., Parlan; Al-Fath, Hanifah Nur (Indonesian Journal of Pharmacy, 2013)
A sulphate polygalactan carrageenan was isolated from Euchema alvarezii Doty with yield 54.36%. The sulphate polygalactan was fractionated with KCl (aq) 2.5% result of a sulphate polygalactan of soluble fraction with the yield 60.34% and a sulphate polygalactanof insoluble fraction with the yield 34.53%. Based on the properties and supported by IR spectrum, the sulphate polygalactan of soluble fraction is k-carrageenan, whilethe sulphate polygalactan of insoluble fraction is l-carrageenan. Anticoagulant activitiy of the carrageenans were based on their prolongation effects on Activated Partial Thromboplastine Time (APTT) and Prothrombine Time (PT) of sodium citrate. On the assays, the carrageenans exhibited promising anticoagulant activities.Key words: Eucheumaalvarezii Doty, k-carrageenan, l-carrageenan, anticoagulant activity, APTT and PT